PENGEMBANGAN MEDIA PEMBELAJARAN CREATING APP BERBASIS TEKNOLOGI AI DALAM PEMBELAJARAN IPAS (PENGENALAN PANCA INDERA BESERTA FUGSINYA) UNTUK MENINGKATKAN PEMAHAMAN KONSEP BELAJAR SISWA KELAS 3 SDN 5 SAPE - Asri Rahmah; Suriya Ningsih M,Pd; Edy Kurniawan, M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an AI-based Creating App learning media in the IPAS subject concerning the introduction of the five senses and their functions to enhance the conceptual understanding of third-grade students at SDN 5 Sape. The method used is Research and Development (R&D) with the Borg & Gall model. Data were collected through validation questionnaires, observations, interviews, and pretests and posttests. The results show that the developed learning media is feasible and effective, with an average N-Gain of 0.75, indicating an improvement in students' conceptual understanding. The use of this media can encourage students to be more active in the learning process.